Quantum Technology and the Medical Librarian - Bengtson, Jason A. (My University, 2015)
Some of the most exciting areas of computing research are quantum technologies. Relying on the counterintuitive laws which govern matter and energy at the smallest levels, quantum physics provides bold new answers to problems which current digital technologies cannot effectively solve. This article discusses the basis of these technologies and introduces two ways in which they may practically impact the environment of the medical librarian in the coming years as the technologies become more mature. By understanding something of these technologies and how they may manifest themselves in hospital or other healthcare environments, the hospital librarian can help prepare themselves for this exciting future.
Citation: Bengtson, Jason. “Quantum Technology and the Medical Librarian." Journal of Hospital Librarianship 15.3 (2015) : 326-333. Print.